Space-Air-Ground Integrated Network Architecture and Transmission Optimization Technology - Siqi HUANG; Deze ZENG; Yuepeng LI; Liangyu ZHANG; Feng GAO (天地一体化信息网络)
With the continuous expansion of application requirements, how to provide efficient networking services in a heterogeneous networking environment integrating space, space and ground have become a new problem.Through the analysis of the application scenarios and technical requirements of the future space-air-ground integrated network, a space-air-ground integrated network architecture based on a software-defined network was proposed to met the requirements of rapid response and collaborative processing.At the same time, it briefly expounded on its main components and transmission optimization technology.Then, the development trends and challenges of the software-defined space-air-ground integrated network architecture were summarized and prospected, which provided a reference for the future development of an space-air-ground integrated network.